Lithic industries and plant processing in the Epipalaeolithic Maghreb: Evidence from use-wear analyses. (30th July 2020) - Gassin, Bernard; Guéret, Colas; Dachy, Tiphaine; Gibaja, Juan F.; Lubell, David; Perrin, Thomas
Abstract: The Holocene hunter-gatherers of the Maghreb are characterized by extensive use of wild plant resources; for food and for making containers, weapons and tools, ropes and fabrics. Some of the harvesting and processing operations of these materials can be performed with stone tools that leave traces on the tools. It is therefore possible to get information about the nature of the harvested and processed plants, the technical operations carried out with the tools and the design of the tools themselves. This information has a technological, economic and cultural scope, and is essential for thinking about the links between environmental changes and lithic industry variability. We present here the first data from technological and use-wear studies carried out on collections from Epipalaeolithic sites in Algeria and Tunisia, focusing on unretouched blades and bladelets from the Columnatian, blades and backed blades from the Typical Capsian, and notched blades and bladelets from the Upper Capsian.